Evaluasi Penyimpanan Obat High Alert Di Instalasi Farmasi Rumah Sakit Juanda Kuningan - Haryadi, Dwi; Trisnawati, Winda (STIKes Muhammadiyah Kuningan, 2022)
ABSTRACT High alert drugs are drugs that cause a high risk when there is an error in the administration. According to Decree No. 72 of 2016 the high alert category became 3, including LASA (Look Alike Sound Alike), High concentration electrolytes and Sitostatic. The purpose of this study is to find out the picture and suitability of high alert drug storage at the Juanda Kuningan Hospital Pharmacy Installation.This study is descriptive, the population and samples in this study are all high alert drugs in the Juanda Kuningan Hospital Pharmacy Installation. Data collection is done using a checklist sheet. Checklist refers to the standard of storage according to PerMenkes RI No. 72 of 2016. The study was conducted in April-May 2021.The results showed high alert drugs in accordance with PerMenkes RI No. 72 of 2016 with a 100% conformity percentage in high alert drug storage, LASA drug storage (Look Alike Sound Alike) or NORUM (Similar Speech Type Drug Name) and storage of Concentrated Electrolyte Concentrate drugs. Keywords : Storage, High Alert Drugs, Juanda Kuningan Hospital Pharmacy Installation